2020
DOI: 10.21037/jtd-20-1247
|View full text |Cite
|
Sign up to set email alerts
|

Hemoptysis complicating ultrasound-guided transthoracic needle lung biopsy: air bronchial sign is a risk predictor

Abstract: Background: Hemoptysis is the most frequently reported complication of ultrasound-guided transthoracic needle lung biopsy (US-TTLB). However, factors influencing the occurrence of hemoptysis as a result of US-TTLB remain uncertain. Therefore, the aim of this study was to evaluate the incidence of hemoptysis as a complication of US-TTLB and to identify the related risk factors. Methods:We retrospectively analyzed all data of patients who underwent US-TTLB from February 2013 through December 2016. The incidence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Regarding CT features of US-guided PCNB-related complications, Zhang et al ( 30 ) reported that 20 of 209 patients had post-procedural hemoptysis, and air-bronchogram on CT was a risk factor for hemoptysis of US-guided PCNB. In this study, only one of 20 patients (5%) with air-bronchogram on CT had post-procedural hemoptysis.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding CT features of US-guided PCNB-related complications, Zhang et al ( 30 ) reported that 20 of 209 patients had post-procedural hemoptysis, and air-bronchogram on CT was a risk factor for hemoptysis of US-guided PCNB. In this study, only one of 20 patients (5%) with air-bronchogram on CT had post-procedural hemoptysis.…”
Section: Discussionmentioning
confidence: 99%
“…The microvessel density (MVD) is considered an early indicator of angiogenesis, and quantitative assessment of MVD is an effective means of determining the angiogenesis of a tumour, which could be used to evaluate the therapeutic efficacy of treatment regimens for malignant tumours (8,9). However, assessment of MVD requires that pathological specimens be obtained through invasive procedures, such as needle biopsy, which may increase the risk of haemoptysis or pneumothorax (10). Some studies showed that several parameters of ultrasound or contrast-enhanced ultrasound (CEUS), such as blood flow velocity and area under the receiver (AUC) operating characteristic curve, were positively correlated with the MVD of tumours, suggesting that it may be possible to assess the MVD of tumours to some degree by ultrasound examination, which would thus allow early evaluation of the efficacy of therapeutic interventions (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Bleeding and pneumothorax are the most common complications of percutaneous US-guided lung biopsy. The incidence of hemoptysis ranged from 0.5 to 22%, and hemothorax is rare [2,3,5,6,[9][10][11]. Air bronchial sign was reported as a risk factor of hemoptysis [11].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of hemoptysis ranged from 0.5 to 22%, and hemothorax is rare [2,3,5,6,[9][10][11]. Air bronchial sign was reported as a risk factor of hemoptysis [11]. The pneumothorax incidence rate ranged from 0 to 5.8%, while the rate of chest tube drainage ranged from 0 to 1% [3,4,12].…”
Section: Introductionmentioning
confidence: 99%